System for recognising and monitoring the technical condition of construction machines - Minh Nguyen Trong; Zorin V.A (E3S Web of Conferences, 2023)
Assessing and predicting machine reliability and failure risks is an essential requirement of international standards for machine safety. The existing methods for determining reliability indicators and risk assessment are based on statistical information about failures and faults that occur during machine operation. Collecting, accumulation and processing of statistical data about failures of machines by traditional methods does not provide the necessary efficiency and reliability of the received information. In this connection forecasting of reliability, estimation, and risk management in production and operation of machines with necessary reliability is not a simple task. Modern diagnostic systems offer unlimited possibilities for the timely acquisition and transmission of information concerning the technical condition of machines, which can be used for the solution of problems. Depending on the structure and location of the transmission, storage and processing of the information, a distinction is made between stationary or remote diagnostics systems. With the modern development of communication and data transmission, remote systems are improved versions of stationary diagnostic systems. In the article the questions of formation of a recognition system and monitoring of a technical condition of building machines by means of the diagnostic information are considered. The main purpose of the development and implementation of the system is to ensure the reliability and safety of operation of construction machines. In order to solve this problem, it is necessary to recognize and promptly prevent the occurrence of failure, which requires the allocation of a special class of intermediate states, called pre-emergency. The results of the implementation of the recognition and monitoring system of construction machines with the help of diagnostic information are presented.